RESULTS OF PHOTOGRAPHIC OBSERVATIONS OF THREE ECLIPSING STARS CD AND, AT MON AND BW CAS - Antonyuk, K. A. (Одеські астрономічні публікації, 2017)
Photometric elements for CD And, AT Mon and BW Cas are presented. The initial epochs for primary minima are 2444469.97(3), 2443598.1295(8)and 2445579.4812(2) respectively, with corresponding period values of 34.4425(7), 4.29405(12) and 2.52563(5) days. Brightness of comparison stars and moments of weakenings are determined. No period changes have been detected.